The Effect of Promotion, Service and Estimated Value to Increase Customer Rate of Gold Pawn Products at PT. Pawnshop UPC Trenggalek - Kusumaningsih, Luki Ayu; Hakimah, Ema Nurzainul (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: Baims to determine the influence of promotion, service and estimated value both partially and simultaneously on customer decisions in choosing gold pawn products on pawnshops Design/Methode/Approach: to answer the problems in this study, a quantitative approach with multiple linear regression analysis tools is used. The population in this study is customers who do gold pawn financing. The sample was determined as many as 80 respondents taken using accidental sampling techniques T test used to determine the variables of promotion, service, and partial estimates against customer decisions. While F test is used to see the effect together of all independent variables to the dependent variable. Research Finding: This study showsthat promotion, service, and value are estimated to have a significant influence on customer decisions in choosing mace products. Theoretical contribution/Originality : Practitionel/Policy implication : Research limitation : Keywords : Gold pawn, promotion, service, estimated value, and customer decision